(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study investigates the impact of the 5E Instructional Model compared to traditional teaching methods on 9th-grade students’ interest, spatial intelligence, and academic achievement in geography in Hyderabad District, Telangana. The 5E model, emphasizing inquiry-based learning through the stages of Engage, Explore, Explain, Elaborate, and Evaluate, is compared to conventional, lecture-based methods. Pretests and posttests were administered to 100 students (50 in each group), assessing their interest in geography, spatial intelligence, and academic performance. The findings indicate no significant difference in students’ interest between the two teaching methods, as both groups showed similar levels of engagement posttest. Furthermore, spatial intelligence scores remained largely unchanged across both groups. Despite the theoretical advantages of the 5E model in promoting deeper engagement and critical thinking, this study suggests that other factors, such as prior knowledge, external influences, and the duration of the intervention, may have impacted the outcomes. The research highlights the need for further investigation into the effectiveness of active learning models in fostering long-term student interest and enhancing spatial intelligence, particularly in geography education.